AWS development fundamentals - Garner, Nick; Safari eBooks ([Place of publication not identified] : Addison-Wesley Professional, 2017)
This video presents an overview of the Amazon Web Services (AWS) and cloud computing. After viewing the video the user should have a firm understanding of: compute instances in AWS, virtual private cloud concepts and deployment, database options, identity and authentication, security constructs, and AWS API.--From video "Success Criteria" screen.
Title from resource description page (Safari, viewed December 5, 2017).
Presenter, Nick Garner.
Keywords: Amazon Web Services (Firm); Cloud computing; Web sites -- Design; Web site development; Electronic books